The Bitmap is the Territory: How Digital Formats Render Global Positions - Geoghegan, Bernard Dionysius (MLN, 2021)
The spatial expanses digital formats assign on the screen are part of a seamless fabric of global technical standards shaping an order of things in lived space. In this light, the latter-day integration of mobile devices with the satellite-enabled global positioning system (GPS) is no incidental supplement to digital devices. When seeing and writing human subjects no longer serve as the guarantors of origin and place, as is the case in Campe's readings, the transition to digital writing appears rather different than some media theorists have supposed. Because digital graphics are encoded and decoded by machines, they have often been viewed as unmoored from sensorial and spatial orientation (Denson). Following a brief discussion of the rendering concept, in the following remarks I consider three scenes in the development of new standards for electronic images: (1) 1940s radar images which encoded the spatiotemporal and social demands of the World War II battlefield, (2) the 1980s development of the JPEG, which hitched visibility to nineteenth-century ideals of international consensus through technical standards, and (3) the development of EXIF metadata, which aligned digital imaging with the exigencies of global markets.